Key factors affecting entrepreneurship and self-employment intentions among social sciences and humanities students - Noor Syakirah Zakaria; Syahruddin Awang Ahmad; Siti Norbayu Yusof; Fauzie Sarjono; Aisah Meri; Zainuddin Baco; Amrullah Maraining (Human Resource Management Academic Research Society (HRMARS), 2023)
The concept of self-employment through entrepreneurial activities needs to be given attention by all parties, especially in helping to solve problems and challenges related to employment opportunities. Therefore, this study aims to examine the factors that influence the self-employment opportunity through entrepreneurial activities. Based on previous studies, there were four identified factors namely self-efficacy, recognition of opportunities, entrepreneurship education and attitudes towards entrepreneurship. For the purpose of this study, a survey was conducted using a questionnaire instrument and involved a total of 111 respondents consisting of year one to year three students from the Faculty of Social Sciences and Humanities. The data of this study was analysed using SPSS version 27 software which involved descriptive analysis, correlation and multiple regression. The findings of the study showed that the factors of self-efficacy and attitude towards entrepreneurship had an established and significant relationship with the intention to be self-employed while opportunity recognition and entrepreneurship education had a moderately strong relationship with intention to be self-employed. The findings also revealed that only two critical factors, namely self-efficacy and attitude towards entrepreneurship had a significant relationship with the self-employment intention while the other two variables; opportunity recognition and entrepreneurship education did not contribute to the intention to be selfemployed. Based on the findings of the study, there is a need to improve the entrepreneurship education system and the exposure on opportunities in entrepreneurial activities that should be strengthened so that students can obtain benefits and knowledge regarding the concept of self-employment through entrepreneurial activities